Autoimmune/Autoinflammatory Syndrome Induced by Adjuvants (ASIA Syndrome) After Polypropylene Mesh Implantation – Protocol of a Pilot Study for Diagnostics and Treatment - M. J. C. A. M. Gielen; M. J. C. A. M. Gielen; M. J. C. A. M. Gielen; K. L. C. van Rest; K. L. C. van Rest; N. D. Bouvy; N. D. Bouvy; G. A. van Koeveringe; C. R. Kowalik; C. R. Kowalik; C. R. Kowalik; C. R. Kowalik; et al. (Journal of Abdominal Wall Surgery)
BackgroundAn increasingly vocal movement of patients with systemic complaints, supposedly linked to polypropylene mesh implants, is leading to increasing numbers of patient-preferred mesh-less surgical repairs for inguinal hernia, stress urinary incontinence, and pelvic organ prolapse. However, current literature does not support any association between polypropylene implants and Autoimmune Syndrome Induced by Adjuvants (ASIA). This prospective pilot aims to examine autoimmunity in patients in whom ASIA is suspected, based on previously described criteria. We aim to demonstrate the effectiveness of mesh allergy testing and to investigate the natural evolvement of ASIA symptoms or the effect of mesh removal on ASIA complaints.MethodsThis multi-centre, prospective pilot study will include patients with symptoms of the ASIA syndrome according to Shoenfeld’s Criteria. Physical examination, immunologic blood tests, and mesh allergy tests will be performed by an experienced immunologist and surgeon. Questionnaires on improvement of symptoms, psychological susceptibility, and connective tissue disease will be collected at predefined time points. When patients’ wish for mesh removal is persistent, mesh implants will be removed surgically. All meshes will be assessed histopathologically. Follow-up is 12 months.DiscussionCurrent evidence on a causal relation between polypropylene mesh and ASIA syndrome is lacking. In this study, mesh allergy testing will be evaluated as a potential first objective screening test for inflammation-like response specific to polypropylene, in patients meeting diagnostic criteria for ASIA syndrome following polypropylene implantation. This study will be performed to add to existing literature on ASIA with polypropylene adjuvants and to help reduce knowledge gaps on diagnosis and prognosis.